AEROBIC FITNESS TREND OF STUDENTS OF THE FACULTY OF SPORT AND PHYSICAL EDUCATION AT THE UNIVERSITY OF BELGRADE - Goran Prebeg; Natalija Mihajlović; Dušan Mitić (Exercise and Quality of Life)
Aerobic fitness, endurance, and cardiovascular endurance are synonyms for workcapacity, which itself is an important prerequisite for the health and life of every man. Thepurpose of this research was to identify the trend of aerobic fitness of students in the last 15years. The Survey method, which implies nonexperimental crossectional research, was used. Theinstrument is UKK 2km, walking test. The total sample consisted of 605 subjects (389 males, 216 females), students of Faculty of Sport and Physical Education, aged 18-28 years. They weredivided into three groups, according to when they were tested, the first group was tested in theperiod 1997-2000 (N = 299), the other was tested from 2001-2004 (N = 200), the third wastested in 2012 (N = 106). Analysis of the results showed a decreasing trend in fitness index ofmale students with 104.1 to 77.3, and of the female students from 96.4 to 84.8. T-tests confirmeddifferences in fitness index, at the level of p<0.05 for both sexes. The maximum oxygenconsumption among male students declined from 51.3 to 40.3 ml/kg/min, and among femalestudents from 37.5 to 33.7 ml/kg/min. The results indicate toward decreasing trend in students' aerobic fitness in both sexes, but the trend is less pronounced in female students. Students ofboth sexes have fitness index values below the standard norms of the Swedish population. According to the criteria of Cooper oxygen consumption students have moved from theìExcellentî to the ìVery goodî category. The general trend of decreasing aerobic fitness of thepopulation can be seen in the sport and physical education students, as a consequence of lifestylein which there is not enough adequate physical activity.